2023
DOI: 10.1007/s10113-023-02078-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate change awareness, perceived impacts, and adaptation from farmers’ experience and behavior: a triple-loop review

Abstract: Individuals and communities socially construct risk, and societies with greater risk perception may be more apt to mobilize or adapt to emergent threats like climate change. Increasing climate change awareness is often considered necessary in the first stages of the adaptation process to manage its impacts and reduce overall vulnerability. Since agriculture is affected by climate change in several ways, farmers can provide first-hand observations of climate change impacts and adaptation options. This paper aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 212 publications
0
5
1
Order By: Relevance
“…Paradoxically, in our case, a high vulnerability perception resulted in farmers' inaction instead of triggering the adoption, which runs counter to what earlier research has found (Arbuckle et al, 2015). Although counterintuitive, it confirms that heightened awareness of climate change might relate to a reduced sense of perceived vulnerability due to risk normalization (Luís et al, 2018), and consequently, a poor risk appraisal may result in maladaptive responses increasing their vulnerability to the impacts of climate change (Deressa et al, 2009;Ricart et al, 2023). Thus, our study adds to the existing body of literature on climate risk perception that such contextspecific climate risks -i.e., coffee leaf rust disease, droughts, or heavy rainfallrelate heterogeneously within the types of technologies understudy.…”
Section: Connecting Climate Risk Coping Appraisal and Secondary Risk ...contrasting
confidence: 91%
See 1 more Smart Citation
“…Paradoxically, in our case, a high vulnerability perception resulted in farmers' inaction instead of triggering the adoption, which runs counter to what earlier research has found (Arbuckle et al, 2015). Although counterintuitive, it confirms that heightened awareness of climate change might relate to a reduced sense of perceived vulnerability due to risk normalization (Luís et al, 2018), and consequently, a poor risk appraisal may result in maladaptive responses increasing their vulnerability to the impacts of climate change (Deressa et al, 2009;Ricart et al, 2023). Thus, our study adds to the existing body of literature on climate risk perception that such contextspecific climate risks -i.e., coffee leaf rust disease, droughts, or heavy rainfallrelate heterogeneously within the types of technologies understudy.…”
Section: Connecting Climate Risk Coping Appraisal and Secondary Risk ...contrasting
confidence: 91%
“…We suggest that a higher perceived risk of the possible consequences of protective behavior may take precedence over the effects of climate threats and coping mechanisms and thus limiting the protective behavior. Moreover, our model broadens the set of explanatory drivers in climate change risk studies (Grothmann & Patt, 2005;Niles et al, 2015;Ricart et al, 2023) and other behavioral models explaining farmers' choices under risks (Bubeck et al, 2012;Joffre et al, 2018;Tabe-Ojong et al, 2020) by showing the relevance of adoption risk perception as a predictor of adoption of new technologies and practices.…”
Section: Connecting Climate Risk Coping Appraisal and Secondary Risk ...mentioning
confidence: 92%
“…To describe the picture in "large strokes", the results identify five groups of the most relevant adaptation measures stimulated by the impacts of climate change. The ASAs in agriculture that can be distinguished at the Local and Region scales are: (i) crop varieties and management, including changes in land use and innovative breeding techniques; (ii) water and soil management, including agronomic techniques; (iii) farmers' education and knowledge transfer; at the Region and Nation scales: (iv) financial schemes, insurance, migration, and culture; (v) agricultural and weather services, R&D, including the development of early warning systems [11,99,138].…”
Section: Discussionmentioning
confidence: 99%
“…The first two sections focused on exploring farmers and farming characteristics, with 10 and 12 categorical/dummy items each, respectively. These variables were selected based on previous studies like Azadi et al (2019), Zhang et al (2020b), Teshome et al (2021) and Ricart et al (2023) for quota sampling. Then, four 'behavioural' sections were defined to delve into independent variables regarding climate change awareness, perceived impacts, and adaptive capacity.…”
Section: Data Collectionmentioning
confidence: 99%
“…Likewise, as stated by Chhetri et al (2019) or Wilson et al (2020), adaptation strategies, whether undertaken independently or collaboratively, can influence farmers' reactions, ranging from making gradual changes to transforming the entire system. This transformation is usually accomplished by using different adaptation strategies at the farm level, considering farmers' heterogeneity (Ricart et al 2023). That is, farmers are nothing but homogeneous (Bartkowski et al 2022); they are a complex and diverse community influenced by different socioeconomic factors and behavioural patterns (Barnes et al 2022).…”
Section: Introductionmentioning
confidence: 99%